2017
DOI: 10.1142/s1758825117500910
|View full text |Cite
|
Sign up to set email alerts
|

Studying Normal and Oblique Perforation of Steel Plates with SPH Simulations

Abstract: Axisymmetric and three-dimensional smoothed particle hydrodynamics (SPH) models are developed to simulate normal and oblique perforation of 12 mm-thick Weldox 460 E steel plates. In the models, a particle-to-particle contact algorithm including friction effect is employed to model interactions between projectile and target plate. A constitutive model coupling viscoplasticity and ductile damage is implemented to describe material behaviors of target plate. Both axisymmetric and three-dimensional SPH models are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Most of the studies have been based on the use of finite element method (FEM), whiles Nair and Rao [23] used 1-D and 2-D discrete element method (DEM). Studies modelling the solid continuum with SPH [24,25] have also found good agreement of results with experimental data.…”
Section: Introductionmentioning
confidence: 54%
“…Most of the studies have been based on the use of finite element method (FEM), whiles Nair and Rao [23] used 1-D and 2-D discrete element method (DEM). Studies modelling the solid continuum with SPH [24,25] have also found good agreement of results with experimental data.…”
Section: Introductionmentioning
confidence: 54%
“…Recent extensions now allow SPH to be used to simulate solid mechanics problems . The natural abilities of SPH to simulate problems involving large deformations make it gain popularity in the modeling of solids in the fields of machining, wear, and resistance to impacts . Indeed, for the simulation of these kinds of problems, true meshfree particle methods, such as SPH, have the advantage over mesh‐based methods such as finite‐element method (FEM) of not requiring a mesh, thus avoiding potentially problematic remeshing when large distortions occur.…”
Section: Introductionmentioning
confidence: 99%
“…This makes TLSPH attractive for the simulation of solids experiencing large deformations coupled with damage. Indeed, TLSPH is being increasingly used to simulate the mechanical response of a ductile material to scratches, impacts, or machining …”
Section: Introductionmentioning
confidence: 99%
“…Due to its abilities to simulate problems involving large deformations, SPH is gaining popularity for the study of the deformations of solids in the fields of machining [3,4], wear [5,6,7], and resistance to impacts [8,9,10,11]. Such popularity has also been fueled by its recent implementation in the opensource particle code LAMMPS [12].…”
Section: Introductionmentioning
confidence: 99%
“…By recalculating the particles' neighbour lists after a few timesteps, they have relied on numerical failure, more specifically the loss of connectivity between neighbouring particles as their distance increase, to account for damage. This so-called "natural ability" for SPH to account for damage has also been used by other researchers [3,7,9,10,11]. However, this is unsatisfactory when it comes to predict the mechanical response of ductile materials experiencing damage.…”
Section: Introductionmentioning
confidence: 99%